The Jossey-Bass handbook of nonprofit leadership and management - Renz, David O. (David Owen); Herman, Robert D., 1946- (Hoboken, New Jersey : Jossey-Bass, A Wiley brand, 2016)
The go-to nonprofit handbook, updated and expanded for today's leader The Jossey-Bass Handbook of Nonprofit Leadership and Management is the bestselling professional reference and leading text on the functions, processes, and strategies that are integral to the effective leadership and management of nonprofit and nongovernmental organizations. Now in its fourth edition, this handbook presents the most current research, theory, and practice in the field of nonprofit leadership and management. This practical, relevant guide is invaluable to the effective practice of nonprofit leadership and management, with expanded attention to accountability, transparency, and organizational effectiveness. It also extensively covers the practice of social entrepreneurship, presented via an integrative perspective that helps the reader make practical sense of how to bring it all together. Nonprofit organizations present unique opportunities and challenges for meeting the needs of societies and their communities, yet nonprofit management is more complex and challenging than ever. This Handbook provides a framework to help you lead and manage efficiently and effectively in this new environment. Building on solid current scholarship, the handbook provides candid, practical guidance from nationally-recognized leaders who share their insights on: -The relationship between board performance and organizational effectiveness -Managing internal and external stakeholder relationships -Financial viability and sustainability and how to enhance both for the long term -Strategies to successfully attract, retain, and mobilize the very best of staff and volunteers The fourth edition of the handbook also includes content relevant to associations and membership organizations. The content of the handbook is supplemented and enriched by an extensive set of online supplements and tools, including reading lists, web references, checklists, PowerPoint slides, discussion guides, and sample exams. Running your nonprofit or nongovernmental organization effectively in today's complex and challenging environment demands more knowledge and skill than ever, deployed in a thoughtful and pragmatic way. Grounded in the most useful modern scholarship and theory, and explained from the perspective of effective practice, The Jossey-Bass Handbook of Nonprofit Leadership and Management is a pivotal resource for successful nonprofit leaders in these turbulent times.
Part one: The context and institutional setting of the nonprofit sector. -- Historical perspectives on nonprofit organizations in the United States / Peter Dobkin Hall -- The legal framework of the nonprofit sector in the United States / Bruce R Hopkins, Virginia C Gross -- The changing context of nonprofit management in the united states / Brent Never -- The many faces of nonprofit accountability / Alnoor Ebrahim -- Part two: Leading and governing nonprofit organizations -- Leadership, governance, and the work of the board / David O Renz -- Executive leadership / Robert D Herman -- Ethical nonprofit management / Thomas H Jeavons -- Strategic management / William A Brown -- Strategic planning and the strategy change cycle / John M Bryson -- Understanding nonprofit effectiveness / David O Renz, Robert D Herman -- Part three: Managing nonprofit operations -- Social entrepreneurship and social innovation / Matthew T A Nash -- Social enterprise and nonprofit ventures / Scott T Helm -- Marketing for nonprofit organizations / Brenda Gainer -- Advocacy, lobbying, and social change / Marcia A Avner -- Value creation through collaboration / James E Austin, M May Seitanidi -- Outcome assessment and program evaluation / John Clayton Thomas -- Part four: Developing and managing nonprofit financial resources -- Financial leadership in nonprofit organizations / Jeanne Bell, Shannon Ellis -- Philanthropy and fundraising / Sarah K Nathan, Eugene R Tempel -- Nonprofit finance / Dennis R Young, Jung-In Soh -- Managing the challenges of government contracts / Stephen Rathgeb Smith -- Tools and techniques of nonprofit financial management / Woods Bowman -- Part five: Leading and managing people in nonprofits -- Effective human resource management / Mary R Watson, Rikki Abzug -- Compensation / Nancy E Day -- Designing and managing volunteer programs / Jeffrey L Brudney.
Includes bibliographical references and index.
Online resource; title from resource home page (Wiley Online Library, viewed March 27, 2019).
John Wiley and Sons
Keywords: Nonprofit organizations -- Management; Associations sans but lucratif -- Gestion; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Nonprofit organizations -- Management